2017
DOI: 10.18844/prosoc.v4i3.2527
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between empathic tendencies and nomophobia of prospective teachers

Abstract: Mobile phone ownership and use is prolific in many countries like Turkey, with the numbers of people owning and using mobile phones rising rapidly in recent years. Nomophobia is the fear of being out of mobile phone contact. The term, an abbreviation for "nomobile-phone phobia", was coined during a study by the UK Post Office who commissioned YouGov, a UK-based research organisation to look at anxieties suffered by mobile phone users. The study found that nearly 53 percent of mobile phone users in Britain tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…Based on the results, it was found that there was a significant negative relationship between self-esteem and nomophobia in students. The results of this finding are consistent with the findings of earlier studies (Argumosa-Villar et al, 2017;Khazaee et al, 2014;King et al, 2013;Yıldırım, 2017). According to these researchers, people with low selfesteem were more likely involved with nomophobia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the results, it was found that there was a significant negative relationship between self-esteem and nomophobia in students. The results of this finding are consistent with the findings of earlier studies (Argumosa-Villar et al, 2017;Khazaee et al, 2014;King et al, 2013;Yıldırım, 2017). According to these researchers, people with low selfesteem were more likely involved with nomophobia.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, as students get older, their nomophobia decreases. This is in line with the findings of Yıldırım (2017) and Pavithra et al (2015) but inconsistent with the results of (Uguz & Bacaksiz, 2022).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation